2016
DOI: 10.1136/bjsports-2016-096309
|View full text |Cite
|
Sign up to set email alerts
|

Training loads and injury risk in Australian football—differing acute: chronic workload ratios influence match injury risk

Abstract: Aims (1) To investigate whether a daily acute:chronic workload ratio informs injury risk in Australian football players; (2) to identify which combination of workload variable, acute and chronic time window best explains injury likelihood. Methods Workload and injury data were collected from 53 athletes over 2 seasons in a professional Australian football club. Acute:chronic workload ratios were calculated daily for each athlete, and modelled against non-contact injury likelihood using a quadratic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(150 citation statements)
references
References 23 publications
7
142
1
Order By: Relevance
“…[9][10][11]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Other timeframes included a 3-day acute load and a 21 daychronic load, 19 or varying timeframes. [37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury. 38 Five studies utilized exponentially weighted moving averages (EWMA) for their calculation of ACWR 17,27,29,36,39 and four articles studied a combination of ACWR and chronic workload.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…[9][10][11]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Other timeframes included a 3-day acute load and a 21 daychronic load, 19 or varying timeframes. [37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury. 38 Five studies utilized exponentially weighted moving averages (EWMA) for their calculation of ACWR 17,27,29,36,39 and four articles studied a combination of ACWR and chronic workload.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…38 Colby et al 30 reported, compared to ACWR range of 0.99 to 1.08, ranges of <0.88 (IRR=1.17), 1.08-1.21 (IRR=1.37), and >1.21 (IRR=1.53) resulted in higher incidence of injury, while 0.88-0.99 (IRR=0.60) resulted in a lower incidence when using TD. This same study found that when compared to an above average chronic TD load (81694m over 4 weeks) and moderate 27,30,34,[36][37][38][39] Total [9,10,17,20,21,[23][24][25][26][28][29][30][31][32][33][35][36][37][38]40] ACWR [11,[17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Association Of External Loads and Injury Risks Total Distancementioning
confidence: 99%
See 2 more Smart Citations
“…While the use of session-RPE as an alternative input of load may be relevant, some substantial limitations remain, such as the lack of sensitivity of RPE to subtle differences in high running speeds. The optimal duration of both the chronic (2 vs 3 vs 4 weeks, based on off-season and preseason durations) and acute (3 vs 7 days, based on matches occurrence) periods of load need probably to be discussed to better fit the specific training/completive patterns of elite football 9. Injury prevention cannot be limited to the monitoring of a single (A/C) number; understanding players' individual needs and profiles, and using common sense when programming workloads are probably as important to keep players fit and healthy.…”
mentioning
confidence: 99%